Manajemen laba melalui manipulasi aktivitas riil di sekitar penawaran saham tambahan dan kinerja perusahaan - ADRIAN YOSUA P; RILYA ARYANCANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
This study aims to determine the effect of earnings management through real activity around additional stock offerings and their impact on the future performance of the company. Real earnings management proxy with sales management activities, increased production and a reduction in discretionary expense. Data were analyzed using multiple regression analysis statistical method. The regression results indicate that increased production activity around the stock offering additional decrease the performance of the company in the next year. While the sales management and a reduction in discretionary spending affect the company's performance in a positive but not significant.